Upaya Meningkatkan Kreativitas Anak Melalui Kegiatan Meronce Menggunakan Media Bahan Alam Pada Kelompok B - Neneng, Neneng; Haryono, Mimpira; Sari, Rika Partika (Journal Of Dehasen Educational Review, 2022)
The purpose of this study was to find out whether through teaching activities using natural material media can increase creativity in group B children in the CEMPAKA PAUD Ujung Padang Seluma Unit. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were 15 children in group B. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing children's creativity through monitoring activities using natural material media in group B children in the CEMPAKA Ujung Padang Seluma PAUD Unit in the first cycle of the first meeting were 71% and in the second cycle of the first meeting there was an increase of 92%. The conclusion of the study that through teaching activities using natural material media can increase children's creativity in group B in the CEMPAKA PAUD Unit, Seluma Regency, it is proven that in cycle II there was a significant increase, the percentage of achievement was 92% with very good development criteria (BSB).